Investment by Large Firms in Argentina - Piris Chavarri, Alvaro (IMF Working Papers; Working Paper ;, 2010)
Strong growth in investment made a key contribution to the economic recovery in Argentina earlier this decade. The paper uses firm-level data to assess changes in financing constraints and the linkages between real investment at the firm level and macroeconomic developments in the real exchange rate and real interest rates. It concludes that several factors explain the performance of investment, including the real exchange rate, the cost of borrowing as well as an easing of financing constraints.